Pengaruh Partisipasi Anggaran Dan Informasi Akuntansi Terhadap Kinerja Manajerial : Komitmen Organisasi, Gaya Kepemimpinan, Ketidakpastian Tugas, Ketidakpastian Lingkungan Dan Strategi Bisnis Sebagai Variabel Moderasi - Adek Latifa Nuraini; - Rosyati (Conference In Business, Accounting, And Management (CBAM), 2012)
The objectives of this research to empirically analyze the influence of budgetary participation and accounting information on managerial performance and to the influence of budgetary participation and accounting information to managerial performance are moderated by organizational commitment, leadership styles, task uncertainty, environmental uncertainty and business strategy. To reach the research target, henced data used primary data, that is data questionaires from 118 managers from general conventional banking which under Bank Indonesia Semarang region. The sampling method used is convenience sampling .The method which is used in testing of this hypothesis are linear regression and Moderated Regression Analysis (MRA). The research concludes that the budgetary participation and accounting information has significant effects for managerial performance. The organizational commitment, leadership styles, task uncertainty, environmental uncertainty and business strategy has significant effects for relationship between budgetary participation and managerial performance. Then the leadership styles, task uncertainty, environmental uncertainty and business strategy has significant effects for relationship between accounting information and managerial performance. However, organizational commitment did not moderate the effects between accounting information and managerial performance. Keywords : budgetary participation, accounting information, managerial performance.